2018
DOI: 10.1177/2056305118793404
|View full text |Cite
|
Sign up to set email alerts
|

Is Civility Contagious? Examining the Impact of Modeling in Online Political Discussions

Abstract: This study examines a way to promote civility in online political discussions through modeling discursive cues. An online experiment ( N = 321) was conducted to investigate the impact of civil and uncivil discursive cues on participants’ mode of discussion. Results show that participants who were exposed to civil cues were more likely to engage in civil discourse themselves, stay on-topic, and offer additional perspectives in their comments. We also found that metacommunication (i.e., talking about the tone of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
0
18
0
2
Order By: Relevance
“…Graf et al (2017) found that experimental participants exposed to comments written in uncivil language were more likely to perceive the commenters less favorably and less likely to trust the information presented in the comments. Han et al (2018) found that participants exposed to civil comments were more likely to post comments that were more civil and more relevant to the topic of the discussion, while participants exposed to uncivil comments tended to comment more on the tone of the discussion.…”
Section: Review Of Empirical Studiesmentioning
confidence: 95%
“…Graf et al (2017) found that experimental participants exposed to comments written in uncivil language were more likely to perceive the commenters less favorably and less likely to trust the information presented in the comments. Han et al (2018) found that participants exposed to civil comments were more likely to post comments that were more civil and more relevant to the topic of the discussion, while participants exposed to uncivil comments tended to comment more on the tone of the discussion.…”
Section: Review Of Empirical Studiesmentioning
confidence: 95%
“…Популярно сочетание опроса, основанного на самооценках, с замером цифровых следов пользователя [16]. В ряде исследований респонденты заполняют анкету и выполняют определенную задачу, в которой онлайн-поведение моделируется и контролируется, например, реакции респондентов на комментарии к новостям [24]. Эксперименты помогают ответить на сложные вопросы, например, о намерениях пользователей участвовать в жизни сообществ.…”
Section: рисунок 1 направления исследований онлайн сообществ в политической коммуникацииunclassified
“…Политическая коммуникация в социальных сетях в силу своей специфики зачастую проходит в ожесточенном ключе: праворадикальные течения используют «язык ненависти» (hate speech) дискриминационного характера (оскорбления, оценочные суждения, сарказм) [5; 57]. Как правило, вежливая дискуссия порождает уважительную реакцию и способствует развитию конструктивной коммуникации, не отходящей от темы [24]. Многие исследователи изучают поляризацию мнений и пользователей по разным вопросам, как, например, по поводу Брекзита и выборов 2016 года в США [15].…”
unclassified
“…Indeed, following social conventions and respecting others allows for the smoother transmission of ideas and information across transdisciplinary boundaries (Della Chiesa, Christoph, & Hinton, 2009). Civility, or a lack thereof, appears to have a contagious effect on communication (Han, Brazeal, & Pennington, 2018), rendering a transdisciplinary endeavour progressively easier or more difficult depending on its presence or absence (Hyun, 2011;Pohl, 2005). Civility has been noted as the answer to the inevitable disciplinary conflicts that arise when conducting transdisciplinary research (Benesh et al, 2015).…”
Section: Is Civility Both the Medium And The Message?mentioning
confidence: 99%